Malaysian secondary school students' willingness to communicate in English - Yeap, Evelyn Ewe Lin (2012)
Poor communication competency among Malaysians has become a national problem as this has affected the performance and employability of Malaysian graduates (Azizan and Chew, 2007). In one of the surveys was by the Ministry of Higher Education (2010) on 10,818 undergraduates, it is found that one out of the three soft skills Malaysian students lack is English language communication skills. Lately, as highlighted in the newspapers, the declining standard of English in the country have been attributed to policies that have not emphasised English in the education system, and students’ lack of interest in learning the language (Azizan and Lee, 2011). Therefore,factors which contribute to Malaysian students’ inability to orally communicate in English have become an important area of study. This study investigates Malaysian students’ willingness to communicate (WTC) in English as a Second Language (ESL) and its relationship to Motivation, and to Self-perceived Communication Competence (SPCC) respectively. The subjects comprised eight hundred and twenty five secondary schools students who were selected using convenience sampling. The data was collected using questionnaires and semi-structured interview. The questionnaires were used to assess students’ perception of their own WTC,SPCC and Motivation, while the interview questionnaire was used to triangulate the data. The data was analyzed using descriptive analysis,Pearson Correlation Coefficient, Multiple Linear Regression, and Hierarchical Multiple Regression. Results show that there is a high, positive, and significant correlation between WTC and SPCC; and an indirect, significant correlation between WTC and Motivation. It is found that both variables significantly contribute to WTC. Between the two, SPCC is found to contribute higher to WTC as compared to Motivation. The findings are discussed in relation to its pedagogical implications.